(3GdhUjI GdQGFbI hGdfUjMI GdaGFbIs - (3SjO eMeO Hf SjO GdeNJGQ GdcfJj,J (B1244 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdeMehO Hcd Lejd hEfi CjgG GdCN GdUGOb hGdeQjO GdeDjO GdQGFb ehUjc HhUjI QH GdYGdejf s
(3BNQgG (B:s
(3aEf SCdJ CMOkG ai MGLI abVfGgG aGTcQg , hEf bUQ adG JYGJHg aJUjQ YOGhI , hcf cGdeDef jWdH GdeYGPjQ , hdG Jcf cGdefGab jWdH GdYjhH s
(3HgG fXGe GdJYbjHIs
(3fSNI bOjeIs
(3cJHJ ebOeJgG HGdMeQI s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJUha hGdBOGH GdTQYjIs